A Stakeholders’ Perspective on Risk Management for Collaborative University-Industry R&D Programs - Fernandes, Gabriela (2021)
University-industry collaborative programs provide special challenges in understanding and expressing the value of risk management (RM) in delivering program and project benefits. This paper presents a methodology for managing the risks in major university-industry R&D programs within a stakeholders' perspective. An ethnographic study was conducted on a multi-million euro university-industry collaboration initiative. The RM methodology identifies, for each of the key stakeholders, the RM activities in the program, which are largely derived from research literature. Empirical research then prioritizes and selects key RM activities. The research is informed using a case study involving one university and one large industrial partner. Empirical research was conducted by researchers who observed, for five years, at close quarters, the challenges of managing risk in major collaborative programs. The developed RM methodology takes a stakeholders' perspective, by identifying, for each of the key three stakeholders - Program Manager, Project Manager and Program and Project Management Officer, the respective RM activities.